Ultrasonic predictors of good ovarian response in infertile poly cystic ovarian disease patients - Elsayed, Mostafa A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Polycystic ovaries is a common endocrinal ovulatory dysfunction; the presented work presented a ultrasonographic predictor markers with scoring system to predict pregnancy rate in PCO. Methods: The presented work is controlled trial comparing two different sets of uterine and ovarian ultrasound markers, done at Zinat Alhyat hospital in Benha Egypt. 100 participants divided into two groups induced for ovulation with minimal stimulation protocol in both, 6 different ultrasonic parameter calculated after induction of ovulation in known PCO patients, Group one with collective ultrasound score more than 6,Group two with ultrasound marker score of less than 6. Results: Regarding the chemical pregnancy when HCG become more than 25 there were 40 out of 50 chemically pregnant in comparison to 25 out of 50 in the second arm with score less than 6 and a p value of 0.001 and a statistically significant difference ,Regarding the clinical pregnancy rate there were 35 cases with proved gestational sacs by ultrasound out of 50 in group one with score more than 6 compared to 18 cases out of 50 in the second group and p value of 0.0007 which was a high significant difference. Regarding miscarriage rate there were one 1 cases out of 35 in group one compared to 5 aborted cases out of 18 in group 2 with p value of 0.006. Conclusions: Certain ultrasonic parameters 3 ovarian and 3 uterine can be highly correlated with ovulation and pregnancy rates in infertile PCO patients.